Pengaruh Perceived Price, Perceived Quality, Dan Self Congruity Terhadap Customer Loyalty Melalui Repurchase Intention Sebagai Variabel Intervening (Studi Pada Konsumen Avoskin Di Shopee Mall) - Agnes Maria Rosia Diana; Nurul Azizah (Journal of Economic, Bussines and Accounting (COSTING), 2024)
The self-care behavior of the community has increased as a result of the stay-at-home policies during the pandemic. Various product variations have started to emerge as a result of significant consumer interest in skincare. Based on this idea, this research aims to analyze the influence of perceived price, perceived quality, and self-congruity on customer loyalty through repurchase intention as an intervening variable. The sampling method used is non-probability sampling with a purposive sampling technique. The sample consisted of 250 respondents who are Avoskin customers making purchases at Shopee Mall. The data analysis technique used is Partial Least Square (PLS). Based on the results of this research, it can be concluded that perceived price (X1) has a positive and significant effect on customer loyalty (Y), perceived quality (X2) has a positive and significant effect on customer loyalty (Y), self-congruity (X3) has a positive and significant effect on customer loyalty (Y), perceived price (X1) has a positive and significant effect on repurchase intention (Z), perceived quality (X2) has a positive and significant effect on repurchase intention (Z), self-congruity (X3) has a positive and significant effect on repurchase intention (Z), and repurchase intention (Z) has a positive and significant effect on customer loyalty (Y). Keywords: Perceived Price, Perceived Quality, Self Congruity, Customer Loyalty, Repurchase Intention